Pengaruh Penggunaan Media Gambar dan Menulis Terpimpin terhadap Peningkatan Siswa dalam Keterampilan Menulis - Imam Purwanto Oktovan; Muhsin Riyadi; Masriah Masriah (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2020)
The purpose of this researchhow much influence the use of Image media and guided writing Methode to increase student Writing Skills in learning Arabic in class XII K MA NU Patrol Indramayu. And One of the factors that influence the success or failure of learning is the teacher. Therefore, teachers must be clever in choosing the right methods so that the expected learning objectives can be achieved to the maximum. One alternative that is used is to apply Image media and guided writing  method in Writing learning. That picture media is one of the learning media that is directed to facilitate students in understanding learning. And Image media and guided writing  method is an effective method, because this method able to provide understanding for students and make them even more enthusiastic in learning, especially in Writing Skills learning. This research uses quantitative methods with the type of pre experiment designmethods with analysis one group pre test-post test. Data collection methods in this study are by observation, tests and Documentation, while data analysis in this study is to use, normality test, homogeneity test t test and hypothesis test. The results of this study are that students'Skill of learning Arabic Writing without using Image media and guided writing  method in the class is with a minimum value of 62, a maximum of 85 with an average of 73.53. students'Skill of learning Arabic Writing with using Image media and guided writing  method in the class with a minimum value of 73, a maximum of 95 with an average of 87, 40. This means that there is an influence of the use of Image media and guided writing  method to increase ability students in the Writing Skills.